Authority of Courts in Implementing Articles 34 and 36 of the UNCITRAL Law and the International Arbitration Law of Iran: Examination and Analysis - Sahar Bazargani, Rassoul Maghsoodpour, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Considering the ever-growing need of traders for international commerce, establishing a proper platform for fasttracking the resolution of disputes in the international arena with an independent arbitration body is of paramount importance.The UNCITRAL Law, known as the UNCITRAL Model Law on International Commercial Arbitration, allows traders to enforce the rulings of the arbitration tribunal of another country by resolving disputes through arbitration. This article seeks to address one of the most fundamental issues of arbitration, namely the authority of the courts to apply for annulment and nonrecognition of arbitral awards, which are predicted in Articles 34 and 36 of the Model Law, Article V of the New York Convention and Articles 33 and 34 of the Iranian Commercial Arbitration Law. This study also seeks to determine under what conditions and rules, the courts, assuming having the required jurisdiction, can disregard the aspects prescribed by law and recognize the arbitral award in the country of origin even if it is annulled in the country of initial award. Two rules supporting this approach were examined in this regard, namely Estoppel and relevance. With a brief glance at the Iranian law, which has recently sought to establish a tribunal body for the annulment and non-recognition of arbitral awards by drafting Article 34 of the International Arbitration Law, the procedure of courts of other countries, including Germany, which adopts a similar approach in not accepting jurisdiction for courts, is scrutinized. Finally, suggestions for resolving conflicts are made by referring to the studied rules, namely the doctrine of Estoppel and the issue of relevance.